Growth and atrophy of neurons labeled at their birth in a song nucleus of the zebra finch. - Konishi, M (1990)
The robust nucleus of the archistriatum (RA) is one of the forebrain nuclei that control song production in birds. In the zebra finch (Poephila guttata), this nucleus contains more and larger neurons in the male than in the female. A single injection of tritiated thymidine into the egg on the 6th or 7th day of incubation resulted in labeling of many RA neurons with tritium. The size of tritium-labeled neurons and the tissue volume containing them did not differ between the sexes at 15 days after hatching. In the adult brain, tritium-labeled neurons and the tissue volume containing them were much larger in the male than in the female. Also, tritium-labeled RA neurons were large in females which received an implant of estrogen immediately after hatching. The gender differences in the neuron size and nuclear volume of the zebra finch RA are, therefore, due not to the replacement of old neurons by new ones during development but to the growth and atrophy of neurons born before hatching. Similarly, the masculinizing effects of estrogen on the female RA are due not to neuronal replacement but to the prevention of atrophy and promotion of growth in preexisting neurons.